Caught between 1945 and 1989: collective memory and the rise of illiberal democracy in postcommunist Europe. Issue 6 (3rd June 2021) - Verovšek, Peter J.
ABSTRACT: Thirty years after 1989 Europe is once again divided, despite 15 years of integration within the European Union. In contrast to the West's liberal conception of internationally constrained democracy rooted in the protection of individual human rights, Central Europe has developed an illiberal version centred on the popular sovereignty of the nation. I argue that these divergent understandings of democracy and the nation-state are rooted in collective memory. Whereas the West's historical imaginary is based on the traumas of Nazism associated with 1945, Central Europe's is dominated by the legacy of communism symbolically signified by 1989. These differing understandings of past teach strikingly different lessons for the present: one focused on the dangers of nationalism, the other on protecting national self-determination from external interference. The future of the EU depends on its ability create a broader historical narrative that can incorporate both the lessons of 1945 and 1989.